Bacterial Inoculation Strategies for the Achievement of Malolactic Fermentation in High-alcohol Wines - Zapparoli, G.; Tosi, E.; Azzolini, M.; Vagnoli, P.; Krieger, S. (South African Journal of Enology and Viticulture, 2016)
The purpose of this work was to study the induction of malolactic fermentation (MLF) in a wine that does not often support malic acid deacidification because of its high alcohol content. Amarone wine, known for its high alcohol content, served as a model. Simultaneous and sequential alcoholic and malolactic fermentation (AF/MLF) were conducted by direct inoculation of bacteria, which resulted in successful MLF in wines containing approximately 16% (v/v) alcohol. At higher ethanol contents, stuck MLF occurred because of growth inhibition. To overcome this technological problem, the performance of bacteria was tested in wine containing approximately 17% (v/v) ethanol using a starter preparation consisting of cells acclimatised in a wine-water solution (1:1) for 24 h and 48 h respectively. Total l-malic acid depletion was recorded when the bacterial cells that had been acclimatised for 48 h were inoculated simultaneously with yeast to conduct AF. The method by which the bacterial cultures are prepared and the time of inoculation affects the efficacy of MLF in high-alcohol wines. The inoculation of yeasts with acclimatised bacteria before AF seems to be a valid strategy to obtain complete MLF in high-alcohol wines.